2004
DOI: 10.1029/2003ja010147
|View full text |Cite
|
Sign up to set email alerts
|

Response of neutral atom emissions in the low‐latitude and high‐latitude magnetosheath direction to the magnetopause motion under extreme solar wind conditions

Abstract: On 11 April 2001 the high velocity and density of the solar wind and the strong southward interplanetary magnetic field moved the dayside magnetopause inside of geosynchronous orbit. The Low Energy Neutral Atom (LENA) imager on the Imager for Magnetopause‐to‐Aurora Global Exploration (IMAGE) spacecraft in the magnetosphere observed significant emission in the magnetosheath direction. The total neutral atom flux from the dayside region, ignoring the neutral solar wind flux directly from the Sun, shows a threefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…When the spacecraft is situated as is shown in Figure 2, the spacecraft would observe clearly neutral hydrogen emitted in the direction of the arrow shown as Emission A. A simple model by Taguchi et al [2004, Figure 5] shows that this kind of emission can be observed as a distinct peak in the distribution of the hydrogen count.…”
Section: Emission Observed By Image/lenamentioning
confidence: 94%
See 2 more Smart Citations
“…When the spacecraft is situated as is shown in Figure 2, the spacecraft would observe clearly neutral hydrogen emitted in the direction of the arrow shown as Emission A. A simple model by Taguchi et al [2004, Figure 5] shows that this kind of emission can be observed as a distinct peak in the distribution of the hydrogen count.…”
Section: Emission Observed By Image/lenamentioning
confidence: 94%
“…Emission B can be parallel to the Sun‐Earth line, and would overlap the Sun signal when the spacecraft is located downstream of Emission B. Emission C can also overlap stronger emission when the spacecraft is located downstream of Emission C. The stronger emission may come from the magnetosheath near the equatorial plane [ Collier et al , 2005; Taguchi et al , 2004]. Hence a spacecraft residing at a somewhat smaller Z than the possible location of the indentation would be suitable for monitoring the cusp.…”
Section: Emission Observed By Image/lenamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the energies, composition, flux, and direction of the ENAs arriving at the observing location provide important information concerning the processes occurring at remote magnetospheric locations (Taguchi et al 2004;Collier et al 2005a;Hosokawa et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“… Taguchi et al [2004a] have shown for an event on 11 April 2001 that an increase in solar wind ram pressure and a strong southward IMF moved the magnetopause inward, resulting in enhanced charge exchange with the Earth's hydrogen exosphere and increasing the flux of the postshocked neutral solar wind by a factor of three. They suggest that low‐energy neutral atoms may be a means of monitoring cusp motion.…”
Section: Introductionmentioning
confidence: 99%